Living a Happy Life and Prosperity for Scavengers - Bonar Hutapea; Tasya Qurrata Ayun; Cherika Cherika; Regina Natashya; Ricka Noviana; Susanthy Soedaryo (Universitas Muhammadiyah Sidoarjo, 2017)
The Social Welfare Issuer (PMKS) is a person or family who, because of an obstacle, difficulty or disruption, can not carry out their social functions and therefore can not establish a harmonious and creative relationship with their environment so that they can not fulfill their (physical, spiritual and social) needs adequate and reasonable (Thamrin, Masril & Sembiring, 2016). This research has a point to find out how an illustration the depth to live happily and prosperous people the scavengers. A method is executed by qualitative narrative, by interview depth and observation. Researchers had conducted interviews with two subjects that work as scavengers. Results in getting is the depth to live happily of both the subject of very simple with the fulfill of needs and there is also social security for them. They could only fulfill their needs by gathering used goods erratic the amounts of each day and it becomes happiness its own for both subject. However in fact what happens is that social services agency and the central administration has not given a guarantee or assistance which could be used by both subject. Researchers advice for governments is to give the assurance that it is set in accordance with law social welfare, so that the scavengers can receive their rights .